2019
DOI: 10.20960/nh.02422
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of pre-sarcopenia from a single selectional cross at C3 region, using CT scans before radiotherapy

Abstract: La carne es un alimento muy bien aceptado por sus propiedades organolépticas. Es fundamental en el desarrollo del ser humano por su alto valor nutritivo. Fuente importante de minerales, vitaminas y proteínas de elevada calidad. Su importancia nutricional está en consonancia con su repercusión económica. En este artículo, y a la luz del comunicado recientemente emitido por la OMS sobre el peligro para la salud, particularmente de cáncer, del consumo elevado de carne roja y/o procesada y dada la alarma social oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
3
8
0
1
Order By: Relevance
“…Several foundational studies demonstrated a strong correlation of L3 and C3 skeletal muscle area in patients with HNC consistent with our findings herein 12,15,24,25 . Abdominal skeletal muscle cross-sectional area is linearly related to total body muscle mass, so we normalized C3 muscle cross sectional area for stature to determine sex-specific thresholds for sarcopenia as previously described 5 .…”
Section: Discussionsupporting
confidence: 92%
“…Several foundational studies demonstrated a strong correlation of L3 and C3 skeletal muscle area in patients with HNC consistent with our findings herein 12,15,24,25 . Abdominal skeletal muscle cross-sectional area is linearly related to total body muscle mass, so we normalized C3 muscle cross sectional area for stature to determine sex-specific thresholds for sarcopenia as previously described 5 .…”
Section: Discussionsupporting
confidence: 92%
“…The number of patient scans used in each study varied, with the majority 24/32 (75 %) having sample sizes <250, with only three studies having much larger cohorts of >800 (51)(52)(53) . The majority (52 %) of papers focused on muscle mass assessment in patients with head and neck cancer (HNC) (seventeen studies (51,52,(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68) ), with ten (32 %) investigating lung cancer (69)(70)(71)(72)(73)(74)(75)(76)(77)(78) and the remaining papers focusing on a mixed tumour cohort of head and neck, lung, breast and colorectal (53,(79)(80)(81)(82) . More detailed characteristics of the studies are shown in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…software packages. Fifteen papers used a cervical vertebral slice (C3) (54)(55)(56)(57)(59)(60)(61)(62)(63)(64)(65)(66)68,80) with most using the study by Swartz et al as the reference for the use of C3, and applying the prediction formula described to the CSA at C3 to predict CSA at L3 (56) . Seven of these studies were conducted at the same institution in the Netherlands where the use of C3 in muscle mass estimation was first investigated (54)(55)(56)(57)59,(66)(67)(68) .…”
Section: C3mentioning
confidence: 99%
See 1 more Smart Citation
“…Un nuevo estudio llevado a cabo en 2019 ha analizado la MM en pacientes con cáncer mediante una TC de radioterapia extensa que englobaba el nivel C3 y L3. Estos hallazgos también han determinado una correlación positiva entre la MM e índice musculoesquelético (IME) a nivel de C3 y L3 (R 2 =0,876 y R 2 =0,805 respectivamente), por lo que permiten diagnosticar la presarcopenia mediante TC a nivel cervical, sin necesidad de realizar una medición a nivel lumbar 15 .…”
Section: Cita Introducciónunclassified